Translation, Cultural Adaptation of the Portuguese Provider Attitudes toward Cardiac Rehabilitation and Referral (PACRR-P) Scale and Assessment of Its’ Measurement Properties - da Cruz, Mayara Moura Alves [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Takahashi, Carolina [UNESP]; Laurino, Maria Julia Lopez [UNESP]; da Cruz, Murilo Reis Alves [UNESP]; Grace, Sherry L.; Ghisi, Gabriela L. M. (MDPI, 2024)
BACKGROUND/OBJECTIVES: Access to cardiac rehabilitation (CR) is contingent upon physician referrals, yet these are often inadequate, particularly in low-resource settings. This multi-method study aimed to translate, culturally adapt, and validate the Portuguese version of the Provider Attitudes toward CR and Referral (PACRR-P) scale, as well as to identify key factors influencing CR referral in a Latin American context for the first time. METHODS: The PACRR was translated into Brazilian Portuguese through a rigorous process involving independent translation, back-translation, and expert panel review to ensure face, content, and cross-cultural validity. A total of 44 Brazilian physicians completed the questionnaire, allowing for an assessment of internal consistency, criterion validity, and convergent validity. RESULTS: The findings confirmed the face, content, and cultural validity of the 20 translated items, with a mean item clarity rating of 4.8/5. The final version included 17 of the original 19 PACRR-P items, with a Cronbach's alpha of 0.73. Referral rates were significantly associated with over one-third of the PACRR-P items, preliminarily supporting the scale's criterion validity, while correlations with the ReCaRe scores further supported its convergent validity. The most prominent barriers to referral were a lack of familiarity with CR site locations, absence of a standard referral form, and lack of automatic referral processes. CONCLUSIONS: The PACRR's validity and reliability among Portuguese-speaking providers are preliminarily supported.